Factor Related to The Incidence of Ascites in Chronic Kidney Disease Patients Undergoing Hemodialysis at RSUD Dr Moewardi Surakarta: A Cross Sectional Study - Yusman, Felizia Alika; Dewi, Ratih Tri Kusuma; Mashuri, Yusuf Ari; Nurhayatun, Evi; Giani, Maia Thalia (UI Scholars Hub, 2020)
Introduction. Chronic kidney disease (CKD) is a global health issue with continuously rising prevalence. Fluid overload is a frequent systemic complication which occurs in CKD patients undergoing hemodialysis (HD). One of clinical manifestation of fluid overload in HD patients is ascites. This study aimed to determine the factors related to the incidence of ascites in CKD patients undergoing hemodialysis. Methods. An observational analytic study with a cross-sectional approach was conducted at Dr. Moewardi Hospital, Surakarta from September until October 2019. The subjects were end-stage CKD patients undergoing HD. Subjects were selected by total sampling technique. Data were obtained from medical records tracking. Furthermore, each variable was analyzed using Chi Square and Independent T-test analysis. P value less than 0.05 is considered statistically significant. Results. A total of 116 subjects were recruited in this study. Incidence of ascites was documented in 24 (20.7%) patients. The comorbid of chronic heart failure (CHF) was found in 23 (19.8%) subjects, where this condition was associated with the incidence of ascites [p = 0.003; PR 2.888 (95% CI=1.476–5.650)]. In the subjects with hypoalbuminemia was also related to higher incidence of ascites [p < 0.001; PR 7.800 (95% CI=3.153 – 19.293)]. Meanwhile gender, age, diabetes mellitus, the levels of hemoglobin, ureum, creatinine serum, albumin, hematocrit, and leukocyte were not associated with ascites in CKD patients undergoing HD (p > 0.05). Conclusions. Factors related to the incidence of ascites in patients with chronic kidney disease who have undergone hemodialysis is chronic heart failure and hypoalbuminemia.